다발성 대장암 간전이 환자의 치료를 위한 새로운 시도 - 주종우(Chong-Woo Chu); 김형철(Hyung-Cheol Kim); 임철완(Cheol-Wan Lim); 신응진(Eung-Jin Shin); 조규석(Gyu-Seok Cho); 유기원(Ki-Won Yu); 송옥평(Ok-Pyung Song); 홍대식(Dae-Sik Hong); 박성진(Seong-Jin Park); 조준희(Jun-Hee Cho); 이혜경(Hae-Kyung Lee); 김희경(Hee-Kyung Kim); et al. (Annals of surgical treatment and research, 2005)
Multiple bilobar liver metastases (MBLM) are the main cause of low resectability in the colon cancer liver metastases. The authors experienced one case of initially non-resectable colon cancer liver metastases. He was curatively and safely treated with a two-stage hepatectomy using the new method of future remnant liver volume growing. A 54-year-old man was referred to our department with the sigmoid colon cancer combined with MBLM, which were checked in two small metastatic lesions in the left lobe and five large sized lesions in the right lobe in the computed tomogram (CT). At first, a laparoscopy-assisted anterior resection was performed. We performed the 1st stage hepatectomy 3 weeks after the colon resection. Intra-operative Ultrasonogram (US) found 9 small superficial metastatic lesions in the left lobe. All that lesions were completely removed by non-anatomical wedge resection. An occlusion balloon catheter was placed in the right portal vein through a small branch of the inferior mesenteric vein at that time. The future remnant liver volume was sufficiently increased 3 weeks after the 1st hepatectomy. A right hepatectomy was safely performed 22 days after the 1st hepatectomy. The patient had received a regional chemotherapy (interleukin2 based immuno-chemotherapy through hepatic artery) for 6 months, then has been receiving a systemic chemotherapy (biweekly Oxaliplatin, leucovorin, plus 5-fluorouracil) without any recurrence evidence. KCI Citation Count: 0